INDIGENOUS PEOPLE KAMPUNG KUTA KABUPATEN CIAMIS: KAJIAN ETNOBOTANI PEMANFAATAN KELAPA (Cocos nucifera L.) - Ryandita, Fira Regina; Hernawati, Diana; Putra, Rinaldi Rizal (UNIVERSITAS PGRI MADIUN, 2020)
Cocos nucifera L. is a plant species from the Areacaceae family which is widely used by the indigenous people of Kampung Kuta, Ciamis Regency. The indigenous people of Kampung Kuta are still upholding the traditions of life to maintain the balance of nature and the local socio-cultural order, but it is very unfortunate that the use of Cocos nucifera L. by the indigenous people of Kampung Kuta has not been documented in writing, so they are afraid of community traditions and local wisdom values. existing ones can be lost. For this reason, this study aims to describe the ethnobotany of the use of Cocos nucifera by the indigenous people of Kampung Kuta. This research was conducted in Kuta Traditional Village in June 2020, this research is a qualitative descriptive study using the phenomenological method, data collection using purposive sampling technique with semi-structured interviews. The informants in this study amounted to 20 people, namely 13 women and 7 men with an informant age range of 30-67 years. The results showed that there were 19 ways to use coconut which were classified into 5 categories of use, namely as a food source, building materials, used as medicinal plants, handicrafts and traditional ceremonies.